Tracking Nature Inscribed: Nature in Rights and Bureaucratic Practice - Ween, Gro Birgit (Nordic Journal of Science and Technology Studies, 2016)
Indigenous people live in places that non-indigenous people generally consider nature. As these peoples’ livelihoods often are in this nature, their lives are frequently bureaucratised in ways that most of us would never encounter. This article describes my long-term effort to find ways to explore such bureaucratic processes in practice as part of my contribution to an environmental anthropology. I describe how I methodologically and theoretically explore such processes by using two examples of my writing, the articles “Blåfjella-Skjækerfjella nasjonalpark: Naturforvaltning som produksjon av natur/sted” and “Enacting Human and Non-Human Indigenous Salmon, Sami and Norwegian Natural Resource Management”. The first text describes Sami reindeer herders fighting the establishment of a national park. The other concerns an attempt of the Directorate of Nature Management to reregulate sea salmon fishing. Comparing these two articles, I show the variety of bits of nature that are materialised in bureaucratic process. Agency within such bureaucratic processes is explored with references to the materialities of the coined terms, texts bits, conventions and other legal references, as well as the numbers produced in the documents. Circulated, these bits of nature certainly influence the outcome of environmental controversies – they can contribute to naturalising particular narratives or foreseen outcomes.